Net Ecosystem Exchanges of Spruce Forest Carbon Dioxide Fluxes in Two Consecutive Years in Qilian Mountains - Bingying Qiao; Lili Sheng; Kelong Chen; Yangong Du (Applied Sciences)
The net ecosystem CO2 exchange (NEE) of spruce forest ecosystems is poorly understood by the lack of measurements of CO2 in the Qilian Mountain of Western China. Thus, we conducted consecutive measurements of CO2 fluxes using tower-based the eddy covariance method from 2021 to 2022. These results indicated that daily NEE of spruce forest indicated a robust temporal pattern ranging from −28.43 to 29.62 g C m−2 from 2021 to 2022. Remarkable carbon sink characteristics were presented from late May to late September. Month accumulative NEE fluxes ranged from −336.57 to 142.22 g C m−2 in two years. Additionally, average carbon sink was 591.51 ± 37.41 g C m−2 in Qilian Mountain. NEE was negatively driven by vapor pressure deficit (VPD) and average air temperature (p < 0.05), as determined using the structural equation model. However, the direct effect coefficient of precipitation on NEE was weak. VPD was positively driven by air temperature and negatively determined by precipitation. In conclusion, a future warming scenario would significantly decrease the carbon sink of the spruce forest in Qilian Mountain.